Desempenho, custos de produção e características de carcaças de cordeiros ½ Dorper Santa Inês, em diferentes sistemas de produção - Macedo, Luiz Gonzaga Pego de (2010)
The experiment was performed in 2007 at two sites in the state of Parana, Brazil: a property named Rancho do Platero, located in the city of Marialva, and the Iguatemi Experimental Farm, belonging to the State University of Maringa. The study evaluated production performance, quantitative carcass characteristics, and identified the components of the production costs during the suckling phase of % Dorper-Santa Ines lambs allotted randomly into five different systems and finished under three diets. Eighty ewes were used along with their respective lambs (35 males and 53 females). The lambs received pelleted feed and mineral salt ad Iibitum according to (NRC, 2007). The ewes had access to pasture or supplementation with coast cross hay depending on treatment, in addition to 0.8 kg/day of commercial concentrate. The treatments during the raising phase were: ewes and lambs in the shed with creep feeding in the shed (ELSCS); ewes on pasture and lambs with creep feeding in the shed (EPLCS); ewes and lambs on pasture with creep feeding on pasture (ELPCP); ewes and lambs on pasture with creep feeding in the shed (ELPCS); and ewes and lambs on pasture with creep feeding in the shed and on pasture (ELPCSP). The diets during the finishing phase were: feedlot with control feed (FCF); feedlot with feed containing linseed (FLF); and semi-feedlot with control feed (SFCF). Slaughter was pre-set at 35 kg live weight. Production performance during the raising phase was influenced (P<0.05) by the different raising systems, the best performance was found for ELPCS with 0.210 kg/day weight gain and weaning weight of 18.87 kg. The averages for the remaining treatments (ELSCS, EPLCS, ELPCP and ELPCSP) were 0.195 kg/day weight gain and 17.390 kg weaning weight. Lambs born in January and February showed 0.210 kg/day weight gain, which was higher than the 0.190 kg/day for March. The 18.53 kg weaning weight for January and 18.70 kg for February were higher than the 17.07 kg reported for the month of March. The lowest production cost was R$ 5.00 per kg of live weight (kg/LW) in the ELPCS system, and the costs for the other systems varied between R$ 5.12 and R$ 7.52 per kg/LW. The main components of the production costs were: 36.10% for feed, 18.47% for return on investment capital, 16.65% for labor and 9.53% for land leasing. The best results at finishing occurred for lambs from the ELPCSP system, with a slaughter age (SA) of 133.60 days; 0.250 kg daily weight gain from birth to slaughter (DWGBS); 0.320 kg daily weight gain at finishing (DWGF), and 63.60 days in finishing (DF). The lambs from the other systems varied between 137.96 and 152.33 days until slaughter weight; 0.210 to 0.230 kg daily weight gain from birth to slaughter; 0.240 to 0.260 kg daily weight gain at finishing; and 67.96 to 82.33 days in finishing. Males performed better than females, as follows: 131.81 and 151.85 days until slaughter weight; 0.240 and 0.210 kg DWGBS; 0.294 and 0.232 kg DWGF; 61.81 and 81.85 DF, respectively. Lambs born in January spent fewer days in finishing and reached slaughter weight sooner, compared to lambs born in February and March, which were similar to one another. The different raising systems influenced carcass characteristics (P<0.05). The EPLCS system featured hot carcass weight (HCW) of 16.97 kg, cold carcass weight (CCW) of 16.60 kg, and commercial yield (CY) of 49.55%; the ELSCS system resulted in 16.49 kg HCW, 16.18 kg CCW, and 49.09% CY. These two systems were superior to the others and similar to one another. The lowest cooling loss (CL) percentage was 1.68% in the ELPCSP system, and the average for the other systems was 1.77%. The best true yield was 55.82% for EPLCS, and the average of the others was 53.13%. The best leg yields were 35.28% for ELPCS and 34.25% for ELPCSP, and the average leg yield for the others was 33.02%. The best shoulder yield was 21.02% for carcasses of lambs born January, and the average for February and March was l9.49%. Rib, ribs under the shoulder, breast and rib point, and loin yields did not differ, with the following averages: 9.67, 8.02, ll.l7; 10.21%, respectively. The finishing diets did not influence the production performance and carcass characteristics. The best results for hot and cold carcass weight, commercial yield, leg yield, and percentage cooling loss were obtained in carcasses of lambs from the system with ewes and lambs on pasture with creep feeding in the shed and on pasture. The best results for leg weight were obtained in carcasses of lambs born in January and February. The best shoulder weight was found in lambs born in January.